How Monetary Policy Affects the Lending and Economic Activity in a Banking System with Excess Liquidity - Saiti, Dashmir; Gockov, GJorgji; Trenovski, Borce (Sciendo, 2021)
Research purpose. The purpose of this paper is to examine the efficiency of the transmission mechanism of the monetary policy in a banking system with excess liquidity. More specifically, it aims to examine how the interest rates of the central bank bills and inflation rate affect total lending and the overall economic activity in the country. For this purpose, the analysis is based on the case of the Republic of North Macedonia, whose banking system has exhibited excess liquidity in the past decade. Design / Methodology / Approach. The paper is based on two different VECM models, analyzing the impact of the central bank bills interest rates and the inflation rate, on lending and real GDP in the Republic of North Macedonia, for the period 2000 – 2019. The analysis also encompasses unit root tests for the variables of interest in order to determine their order of integration and choose appropriate statistical methods. The short-run causality is assessed using the Granger causality test, whereas the existence of the potential long-run relationship is examined using the Johansen cointegration test. In addition, in order to determine the magnitude of the mutual relationship, variance decomposition is employed in both estimated models. Moreover, the stability of the models when exposed to external shocks is observed through their impulse response functions. Findings. Conducted analysis shows the negative long-term impact of the central bank bills interest rates on lending and real GDP in North Macedonia. However, no statistically significant impact in this regard is found in the short run. Opposingly, the inflation rate negatively affects lending and real GDP in North Macedonia in the short run, whereas, in the long run, it does not have a statistically significant impact. Originality / Value / Practical implications. Unlike many other studies in this area, this paper provides practical guidance for the monetary authorities in countries with excess liquidity in the banking system. Namely, its findings imply that central banks should reduce the interbank rate when faced with crises that cause liquidity disparities between banks. Failure to reduce interest rates during the crisis disrupts financial stability, which causes banks to withhold investing their liquid assets in the real economy.
Keywords: interest rates of the central bank bills, inflation, total lending, real GDP, monetary policy